Autologous serum skin test for evaluation of chronic idiopathic urticaria patients: a tertiary hospital study from central India - Rathoriya, Shyam Govind; Soni, S; Yesikar, Veena; Mahavar, P (International Journal of Medical Research and Review, 2015)
Background: Majority of patients with chronic urticaria, having no definite etiology are considered chronic idiopathic urticaria (CIU). In recent years, relatively significant number of chronic idiopathic urticaria patients has been classified as having autoimmunity on the basis of presence of auto antibodies (IgG anti IgE receptor alpha subunit or less frequently IgG anti IgE itself) which are responsible for mast cell and basophil activation. Material and Methods: A hospital based crosssectional study was carried out in the Department of Skin, Chirayu Medical College and Hospital, Bhopal located in central India, during the period from August 2012 to February 2014 after institutional ethics committee approval. Total 53 Patients in the age range of 16 to 65 years of CIU were enrolled for study after detailed clinical history and physical examination. Results: Out of total 53 patients, 23(43.39%) showed wheal/ swelling of 1.5 mm or larger at test site as compared to that of control site, thus considered as ASST positive. Duration of CIU ranged from 4 months to 11 years with mean duration of 6.13±2.25 years. 19(82%) of the patients had lesions over whole body whereas only 4(17%) had lesions over face and limbs. 10(43%) patients had angioedema and 14(60%) had dermographism. Conclusion: ASST is simple, cheap and effective diagnostic method to detect presence of autoimmunity in CIU patients thus helps in identifying severity of disease and to choose appropriate therapeutic options accordingly. Our study did not elicit distinct clinical parameters of CIU (except number of wheals/ swelling and frequency of lesions, though statistically not significant) in ASST positive patients from those patients who didn’t show ASST positivity.